Application of R-Functions Theory to Study Parametric Vibrations and Dynamical Stability of Laminated Plates - Kurpa, Lidiya; Mazur, Olga; Tsukanov, Igor (Точка, 2013)
The problem of nonlinear parametric vibrations and stability analysis of the symmetric laminated plates is considered. The proposed method is based on multimode approximation of displacements and solving series auxiliary linear tasks. The main feature of the work is the application of the R-functions theory, which allows investigating parametric vibrations of plates with complex shape and different boundary conditions.
Keywords: R-function method; laminated plates; parametric vibrations